Chicken soup for the soul : random acts of kindness : 101 stories of compassion and paying it forward - Newmark, Amy (Chicken Soup for the Soul, 2017)
A collection of 101 uplifting, true stories will help you see the hidden heroes around you and inspire you to be a hero in someone else's life. From random acts of kindness to doing what's right, this book shows how positive attitudes and good deeds can change the world